Insights into the Chalcogen Bonding Catalysis on the ${\rm CO}_2$ Fixation with Styrene Oxide (Communications in Computational Chemistry, 2025)
The fixation of ${\rm CO}_2$ is a promising carbon-neutral approach anddrawing lots of attention in the past decades. Among lots of fixation of ${\rm CO}_2$ methods, the cycloaddition of ${\rm CO}_2$ into epoxides (CCE) reaction is importantbecause it could generate high value-added products. Recently, employingchalcogen bonding (ChB) catalysts for the CCE reaction has been proposed andoffers significant advantages of low price, environmental friendliness, and easeof recycling. In this work, the ChB catalyzed the CCE reaction is investigatedby high level theoretical calculations. The reaction can be divided into three subprocesses: ring-opening, nucleophilic addition, and formation of cyclic carbonate. Both Se- and Te-based ChB catalystshave shown the potential for catalyzing the CCE reaction, the overall catalytic performance of Te-based catalysts wassuperior to the Se-based ones. Overall, the most positive electrostatic potentials of the ChB catalysts, electrostatic term ofthe ChB binding energies, electron density at the ChB critical points, and electron density difference play important rolesin the ChB catalyzed CCE reaction. This work elucidated the ChB catalyzed mechanism of the CCE reaction and providedtheoretical guidance for the future development of efficient ChB catalysts for the CCE reaction.
Keywords: chalcogen bonding catalysis; ${\rm CO}_2$ fixation; density functional theory; QTAIM